Inquiry-Oriented Learning in Science : Transforming Practice through Forging New Partnerships and Perspectives : Final Report. - Kirkup, Les (Office for Learning and Teaching, 2013)
Final report of a Teaching Fellowship at the University of Technology Sydney. This Fellowship focused on facilitating transformation of practice towards inquiry-oriented learning (IOL). It sought to play a prominent role in shaping the national conversation on IOL in the undergraduate science curriculum, especially for large enrolment classes. The research activities involved groups of academics from universities across Australia as well as the CSIRO, and direct input from students through focus groups, hands-on resource trials and a national forum.